Answer:
![f(n)=-0.5* f(n-1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/hxa4jhb1wn6f2qzb1w22simrp9m29vq3b7.png)
Explanation:
Sequence: 9.6, –4.8 , 2.4, –1.2, 0.6, ...
So, f(1) = first term = 9.6
r = common ratio =
![(-4.8)/(9.6) =(2.4)/(-4.8) = -0.5](https://img.qammunity.org/2019/formulas/mathematics/high-school/yi5bw8rlwbftjyy5k6mb9e44xzkij67rmk.png)
Now , formula of nth term in G.P. =
![f(n)=f(1)* r^(n-1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/xxjmfmbqj0lqwhufd83r50nkccgvpq5qjk.png)
So, formula for nth term of the given sequence =
![f(n)=9.6* (-0.5)^(n-1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/ue712qvpf4oq4wkg31zeh7vpqed3i5u3g8.png)
So,
![f(n-1)=9.6* (-0.5)^(n-1-1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/jackzsthshob6zws4hrgi41xaizjfur4ce.png)
![f(n-1)=9.6* (-0.5)^(n-2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/4mh0tbk763p7046uh6k2ekgovj9w4mmlyl.png)
Recursive formula :
![(f(n))/(f(n-1))= (9.6* (-0.5)^(n-1))/(9.6* (-0.5)^(n-2))](https://img.qammunity.org/2019/formulas/mathematics/high-school/xyyx325a95oi3599d50ckyndvsossd1azr.png)
![(f(n))/(f(n-1))=(-0.5)^(n-1-(n-2))](https://img.qammunity.org/2019/formulas/mathematics/high-school/2l68et0eiy4bbzb3hc3lyxdon2dp5s8ogj.png)
![(f(n))/(f(n-1))=(-0.5)^(-1+2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/eix8w85vqqnprl0h8ohua0z00rtb9qs19r.png)
![(f(n))/(f(n-1))=-0.5](https://img.qammunity.org/2019/formulas/mathematics/high-school/qpobp5pyq34m8q157iqvmsl46dr456qi58.png)
![f(n)=-0.5* f(n-1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/hxa4jhb1wn6f2qzb1w22simrp9m29vq3b7.png)
Hence recursive formula can be used to generate the sequence shown, where f(1) = 9.6 and n > 1 is
![f(n)=-0.5* f(n-1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/hxa4jhb1wn6f2qzb1w22simrp9m29vq3b7.png)